2023
DOI: 10.1186/s13293-023-00519-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and age-related differences in renal and cardiac injury and senescence in stroke-prone spontaneously hypertensive rats

Abstract: Background Sex differences play a critical role in the incidence and severity of cardiovascular diseases, whereby men are at a higher risk of developing cardiovascular disease compared to age-matched premenopausal women. Marked sex differences at the cellular and tissue level may contribute to susceptibility to cardiovascular disease and end-organ damage. In this study, we have performed an in-depth histological analysis of sex differences in hypertensive cardiac and renal injury in middle-aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…141–144 Any relative restriction of tubular function about glomerular filtration rate might thus align the excretion behaviors of CRN and TWuAs, translating into an approximation of b to 1. Age-related tubular renal damage progresses faster in males than in females, 136139 which could conclusively explain the reemerging male-dominant age gap in exponents b at higher ages, as illustrated in Figure 6.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…141–144 Any relative restriction of tubular function about glomerular filtration rate might thus align the excretion behaviors of CRN and TWuAs, translating into an approximation of b to 1. Age-related tubular renal damage progresses faster in males than in females, 136139 which could conclusively explain the reemerging male-dominant age gap in exponents b at higher ages, as illustrated in Figure 6.…”
Section: Discussionmentioning
confidence: 82%
“…This inconsistency in men could be due to different age group distributions in the studies or intrinsic renal aging mechanisms, which are more pronounced in men and cause fluid homeostasis inelasticity, such as declining renal prostaglandin levels and tubular dysfunction. [134][135][136][137][138][139] While ATII/AVP activities increase with age, the paradoxical urinary concentrating ability deficit in seniors is likely due to these intrinsic renal causes. 135,140 In conclusion, the age-and sex-specific variations of exponent b consistently reflect the renal baseline actions of ATII/AVP, influenced by sex hormones in the young and renodegenerative changes in the elderly, irrespective of the age-related decline in renal concentrating capacity.…”
Section: Pivotal Role Of Osmoregulation In Age-and Sex-variations Of ...mentioning
confidence: 99%
“…Finally, the female sex could be a protective factor to delayed the progression of the renal damage. Recently, Ansari et al [ 51 ] showed a sex and age-related progression of renal fibrosis. Specifically, no differences in renal fibrosis indices were observed between female rats at 6.5 and 8 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, no differences in renal fibrosis indices were observed between female rats at 6.5 and 8 months of age. In contrast, female showed a protective effect from renal damage in relation to age-matched males [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, males are at a higher risk of developing cardiovascular disease compared to age-matched premenopausal women. Moreover, male hypertensive rats displayed greater levels of fibrosis in the heart and kidney compared to female rats ( Ansari, Walton & Denton, 2023 ). However, the understanding mechanisms by which hypertension induces end-organ damages are not completely understood.…”
Section: Introductionmentioning
confidence: 96%